SOME CONSIDERATIONS ABOUT THE WORD WATER AND ITS MEANINGS (Academicia Globe: Inderscience Research, 2021)
The article discusses that the concept of a word is a very complex and multifaceted phenomenon due to its linguistic nature and the word water has three main features like all words which combine all its features.